Influencer Marketing dan Marginal Propensity to Consume (MPC) Generasi Z Indonesia: Mediasi Impulsive Buying Tendency dan Moderasi Financial Literacy - Fitriyah Dina Fatmawati; Humaidah Muafiqie (Yayasan Lentera Avanya Nagari, 2026)
This study examines the effect of influencer marketing on the Marginal Propensity to Consume (MPC) of Generation Z in Indonesia, incorporating the mediating role of impulsive buying tendency and the moderating role of financial literacy. A quantitative cross-sectional design with Partial Least Square – Structural Equation Modeling (PLS-SEM) was employed. The results demonstrate that influencer marketing positively and significantly affects MPC both directly and through the partial mediation of impulsive buying tendency. These findings confirm that influencer content exposure not only shapes purchase intention but measurably shifts the proportion of Generation Z's income converted into actual consumption. Conversely, financial literacy does not moderate the relationship between influencer marketing and impulsive buying tendency, indicating a significant knowledge-behavior gap within this segment. This study contributes an integrative framework bridging Keynesian consumption theory and digital marketing theory within Indonesia's digital economy context.